2013
DOI: 10.1063/1.4808460
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hardness of graphene and MoS2 field effect devices against swift heavy ion irradiation

Abstract: We have investigated the deterioration of field effect transistors based on twodimensional materials due to irradiation with swift heavy ions. Devices were prepared with exfoliated single layers of MoS 2 and graphene, respectively. They were characterized before and after irradiation with 1.14 GeV U 28+ ions using three different fluences. By electrical characterization, atomic force microscopy and Raman spectroscopy we show that the irradiation leads to significant changes of structural and electrical propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 45 publications
8
64
0
Order By: Relevance
“…The graphene samples were then transferred to a vacuum chamber and irradiated with swift heavy ions (Xe 26+ , 91 MeV) using a fluence of 65.000 ions/µm 2 at normal angle to the graphene plane. Under grazing-incidence irradiation these projectiles cause extended modifications in graphene 30,31 , while at normal incidence point-like defects are created 32 . Due to their high energy, the interaction of swift heavy ions with matter is exclusively by inelastic scattering.…”
Section: Methodsmentioning
confidence: 99%
“…The graphene samples were then transferred to a vacuum chamber and irradiated with swift heavy ions (Xe 26+ , 91 MeV) using a fluence of 65.000 ions/µm 2 at normal angle to the graphene plane. Under grazing-incidence irradiation these projectiles cause extended modifications in graphene 30,31 , while at normal incidence point-like defects are created 32 . Due to their high energy, the interaction of swift heavy ions with matter is exclusively by inelastic scattering.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Introducing transition metal (TM) impurities during chemical synthesis can hardly circumvent producing intrinsic defects. 16 Alternatives were suggested e.g.…”
mentioning
confidence: 99%
“…Recently, O. Ochedowski et al have reported the observation of about 50-nm-diameter hillock on monolayer MoS 2 irradiated with 1.14 GeV U 28? ions [13]. However, SHIs irradiation-induced modification of the properties of mono-and few-layer MoS 2 has not been reported yet.…”
Section: Introductionmentioning
confidence: 98%